Surgical retrieval of a guide wire lost during central venous catheterization in a dog. Issue 3 (3rd March 2017) - Hardy, Jade M.; Lansdowne, Jennifer L.; Himsel, Carol A.; Freer, Sean R.
Abstract: Objective: To report a case of successful surgical removal of a guide wire lost during central venous catheterization. Case Summary: A 28 kg, 4‐year‐old female neutered mixed breed dog presented to the primary care veterinarian with diabetic ketosis. During the process of central venous catheterization, the guide wire was accidently released and the entire length of the guide wire slipped into the jugular vein. Due to the absence of nearby interventional radiology facilities, surgical intervention was proposed. An ultrasound was used to determine that the guide wire was located in the caudal vena cava extending caudally into the right internal iliac vein. Rommel tourniquets were placed around the iliac vein cranial to the bifurcation of the common iliac vein into the external and internal iliac veins. A venotomy was performed in the right common iliac vein and the guide wire was grasped with hemostats and gently removed while alternately relaxing the cranial then caudal tourniquets. During anesthesia, ventricular premature contractions were noted that varied in frequency with the dog's positioning. Postoperative color flow Doppler ultrasound evaluation of the caudal vena cava, right common, internal and external iliac veins, and right femoral vein was normal with no evidence of thrombosis. Several days postoperative the dog's diabetic ketosis and ventricular premature contractions had resolved and color flow Doppler ultrasound evaluation was normal with no evidence of thrombosis. New or Unique information provided: To the authors' knowledge, this is the first reported veterinary case of loss and subsequent surgical retrieval of a central venous catheter guide wire.